2012
DOI: 10.5796/electrochemistry.80.774
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Magnesium in Mixed Solutions Consisting of Ionic Liquid and Alkylmagnesiumbromides with Different Alkyl-Chains

Abstract: Electrochemical deposition and dissolution of magnesium have been investigated in organic solutions consisting of alkylmagnesiumbromides/tetrahydrofuran (RMgBr/THF) having different alkyl-chains mixed with an ionic liquid. Coulombic efficiency for cathodic deposition and anodic dissolution of magnesium, obtained from voltammetric responses, decreased with the increase in the alkyl-chain length of the magnesium complex. The highest current response was observed in the electrolyte system consisting of CH 3 MgBr/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Kakibe et al 122 had similar success using the bis(fluorosulfonyl)imide [FSI] anion and the same cation in a Grignard solution (MeMgBr-THF), finding that the FSI anion was most effective at improving the cycling efficiency to above 90% when combined with the NTf 2 anion explored previously. Similar results were also published earlier the same year in a study by Yoshimoto et al 124 who studied the effect of the alkyl chain on the Grignard molecule. Like Kakibe et al, 122 it was found that MeMgBr-THF with [N 1,2,2,102 ][NTf 2 ] yielded conductive solutions that supported efficient cycling of magnesium metal.…”
Section: Magnesium-airsupporting
confidence: 88%
See 2 more Smart Citations
“…Kakibe et al 122 had similar success using the bis(fluorosulfonyl)imide [FSI] anion and the same cation in a Grignard solution (MeMgBr-THF), finding that the FSI anion was most effective at improving the cycling efficiency to above 90% when combined with the NTf 2 anion explored previously. Similar results were also published earlier the same year in a study by Yoshimoto et al 124 who studied the effect of the alkyl chain on the Grignard molecule. Like Kakibe et al, 122 it was found that MeMgBr-THF with [N 1,2,2,102 ][NTf 2 ] yielded conductive solutions that supported efficient cycling of magnesium metal.…”
Section: Magnesium-airsupporting
confidence: 88%
“…29,117,118 Early studies developing electrolytes for reversible magnesium processes were centred on Grignard type chemicals of the formula RMgX (where R = alkyl, aryl group and X = halide) or similar, dissolved in an organic solvent such as tetrahydrofuran (THF) or diethyl ether. [121][122][123][124][125] Unlike the previously discussed ethereal solutions, many RTILs are reactive to the magnesium metal surface and form a layer of breakdown products. 120 While these novel organic magnesium-stable electrolytes are adequately conductive and have high electrochemical stability, they remain volatile.…”
Section: Magnesium-airmentioning
confidence: 99%
See 1 more Smart Citation
“…22,26 Consequently, several studies using ionic liquids as supporting electrolytes for room temperature Mg reduction in THF containing Grignard Reagents have been reported. 17,19,27,28 In these studies, it has been shown that the conductivity of the media was enhanced considerably. 19 Notably, in 2010, Yoshimoto et al 28 developed a novel Mg electrolyte system consisting of Grignard Reagent and the ionic liquid diethylmethyl (2-methoxyethyl) ammonium bis(trifluoromethylsulfonyl)imide ([DEME][TFSI]).…”
mentioning
confidence: 96%
“…In 2012, these authors introduced a mixed electrolytic medium consisting of a Grignard Reagent (R-MgBr/THF) having variable alkyl-chains, mixed with [DEME][TFSI] ionic liquid. 27 With this approach, it was found that the coulombic efficiency for cathodic deposition and anodic dissolution of Mg decreased with increase in the alkyl-chain length of the Grignard ) were also introduced to further optimize the electrochemically important properties such as viscosity and conductivity. 17 In parallel, this group also optimized the cation structure present in the imidazolium based ionic liquid.…”
mentioning
confidence: 99%